Diffusion and Adoption of Livestock Deworming Technology in Different Agro-climatic Regions of India - Mahesh Chander , H R Meena , Hema Tripathi , Sanjay Kumar , R S Rathore , P S Banerji , K. Pachaiyappan and Prakashkumar Rathod, (Indian Journal of Extension Education, 2015)
Livestock technologies are generated in various research institutions with the notion to explore the possibilities ofuplifting the livelihoods of farming communities. It is generally perceived that the extent of absorption of thesetechnologies in field conditions has always been a researchable issue in India. In this situation, an effort was made to studythe diffusion and adoption status of deworming technology in different agro-climatic zones of India using primary andsecondary data collected from various accessible resources. Group discussion and personal communication withveterinary officers and other experts was also conducted to gain insight and evolve action plans for effective adoption anddiffusion of deworming. The study concluded that there was lack of awareness and poor adoption of deworming due tovarious constraints faced by farmers in deworming. The study suggests that there is a better scope for improving thediffusion and adoption of livestock deworming by means of addressing these constraints and creating favourability oflivestock farmers towards livestock deworming technology.